2016
DOI: 10.1038/srep26760
|View full text |Cite
|
Sign up to set email alerts
|

Different dietary patterns and reduction of lung cancer risk: A large case-control study in the U.S.

Abstract: Reducing lung cancer risk by modifying diet is highly desirable. We investigated whether different U.S. dietary patterns were associated with lung cancer risk. Dietary patterns were derived using exploratory factor analysis for 2139 non-small cell lung cancer (NSCLC) cases and 2163 frequency-matched controls. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs). Highest adherence (highest vs. lowest quintile) to the “Tex-Mex”, “fruits and vegetables”, and “American/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 46 publications
1
32
1
Order By: Relevance
“…Our association findings for four patterns are consistent with findings from previous studies on dietary pattern and lung cancer. Previous factor-analysis studies [ 15 17 ] have related healthful eating to a decreased risk of lung cancer, similar to findings obtained with index-based dietary patterns, supporting the current dietary guidance of increasing consumption of fruits, vegetables, whole grains, lean meats or meat alternatives, and low-fat dairy [ 11 ]. In addition, the Mediterranean dietary pattern was thought to be negatively related with risk of lung cancer, whereas a “Western” dietary pattern was found to be associated with lung cancer risk [ 13 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our association findings for four patterns are consistent with findings from previous studies on dietary pattern and lung cancer. Previous factor-analysis studies [ 15 17 ] have related healthful eating to a decreased risk of lung cancer, similar to findings obtained with index-based dietary patterns, supporting the current dietary guidance of increasing consumption of fruits, vegetables, whole grains, lean meats or meat alternatives, and low-fat dairy [ 11 ]. In addition, the Mediterranean dietary pattern was thought to be negatively related with risk of lung cancer, whereas a “Western” dietary pattern was found to be associated with lung cancer risk [ 13 ].…”
Section: Discussionsupporting
confidence: 71%
“…Although intake of vegetables and fruits has been suggested to reduce the risk of lung cancer [ 10 ], β-carotene (BC)—a retinal (form of vitamin A) precursor found in many edible plants—has been suggested to increase the risk of lung cancer in smokers [ 7 ], perhaps due to a complex gene-diet interaction. In this regard, Tu and colleagues suggested recently that the association between dietary patterns and lung cancer risk may be modified by genetic background [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Tex‐Mex pattern is based on an American regional cuisine which is quite specific for the area where our study was conducted. Except for two studies on renal cancer risk and lung cancer risk, no studies reported about this pattern before. The Tex‐Mex pattern contains potentially beneficial components such as legumes, as well as potentially harmful components such as red meat and pizza.…”
Section: Discussionmentioning
confidence: 99%
“…The research in the world on the relationship between dietary patterns (DPs) and lung cancer, particularly the effects of the Mediterranean diet, is ambiguous and limited. Many studies have investigated the associations between dietary patterns and lung cancer risk [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Though the findings are not definitive, the majority of these studies suggest that a healthy diet is associated with a decreased risk of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the effect is not due to single nutrients, but to a complex of components with synergistic and antagonistic interactions [ 47 ]. However, the evidence is still limited, because there are still only a few studies (including one study of Polish men) focusing on dietary patterns [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and the Mediterranean diet [ 34 , 44 , 45 , 46 , 47 ] and the risk of lung cancer. To the authors’ knowledge, no studies have so far been published assessing the relationship between dietary patterns and the risk of lung cancer in Polish men who smoked moderately or heavily.…”
Section: Introductionmentioning
confidence: 99%